Art outside insulation - K. R. Radyk (Ukrainian Cultural Studies, 2021)
When the alarming and shaky topic of the post-quarantine future is touched upon in conversation, someone inevitably voices the idea that "the world will never be the same." It is difficult to argue with this, but in such a case, panic should have been announced earlier: the world was supposed to change even without quarantine.